Uji Efektivitas Khitosan terhadap Daya Awet Ikan Nila (Oreochromis niloticus) - Rina Sugiarti Dwi Gita; Hepta Bungsu Agung Jayawardana; Ahmad Afandi (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the effect of the application of chitosan on fresh tilapia (Oreochromis niloticus) products as a natural preservative that can maintain the condition of fish with a longer shelf life. The method used in this study was experimental with three treatments, namely control treatment, 1% chitosan coating, and 1.5% chitosan coating. Data analysis was carried out through organoleptic tests with four parameters: color, aroma, texture, and taste of the tested tilapia. Observations were made for three consecutive days. The results showed that tilapia with 1.5% chitosan coating had better organoleptic parameter values than the other two test treatments. In conclusion, 1.5% of chitosan maintained the quality of tilapia with a longer shelf life. Keywords: Durability, Tilapia, Chitosan, Organoleptic